2021
DOI: 10.1002/ejp.1866
|View full text |Cite
|
Sign up to set email alerts
|

Five‐year observational study of Internet‐delivered cognitive behavioural pain management when offered as routine care by an online therapy clinic

Abstract: Background: Internet-delivered cognitive behavioural pain management programmes (PMPs) are effective, but less is known about their use outside of research trials. Five years of data from offering the Internet-delivered cognitive behavioural PMP in an online therapy clinic was examined to assess effectiveness, acceptability and predictors of outcomes.Methods: Patients (N = 293) were offered a previously validated 8-week Internet-delivered cognitive behavioural PMP and administered measures at pre-treatment, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…When reflecting on barriers or challenges experienced during the course, clients expressed a desire for alternative delivery options (e.g., podcasts or audio clips) and additional therapist contact options (e.g., telephone check-ins or more frequent contact). Nevertheless, it should be noted that previous studies of ICBT have found that offering telephone check-ins are associated with implementation challenges, including requiring clients to make time during their day to schedule a synchronous phone call ( Hadjistavropoulos et al, 2021 ) and that more frequent contact beyond once weekly contact (e.g., response within one business day; Hadjistavropoulos et al, 2020a ) does not result in better outcomes. Although, these options for therapist support have not been examined in a sample of agriculture producers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When reflecting on barriers or challenges experienced during the course, clients expressed a desire for alternative delivery options (e.g., podcasts or audio clips) and additional therapist contact options (e.g., telephone check-ins or more frequent contact). Nevertheless, it should be noted that previous studies of ICBT have found that offering telephone check-ins are associated with implementation challenges, including requiring clients to make time during their day to schedule a synchronous phone call ( Hadjistavropoulos et al, 2021 ) and that more frequent contact beyond once weekly contact (e.g., response within one business day; Hadjistavropoulos et al, 2020a ) does not result in better outcomes. Although, these options for therapist support have not been examined in a sample of agriculture producers.…”
Section: Discussionmentioning
confidence: 99%
“…Reliable improvement, recovery, and deterioration were examined to assess for clinically significant changes in symptom scores. Consistent with previous ICBT research ( Dear et al, 2015a , Dear et al, 2015b ; Titov et al, 2020 ; Hadjistavropoulos et al, 2021 ), reliable improvement was defined as scoring ≥ 10 on the PHQ-9 or ≥8 on the GAD-7 at pre-treatment and scoring at least 6 points on the PHQ-9 or 5 points on the GAD-7 lower at post-treatment. Reliable deterioration was defined as an increase from pre- to post-treatment of 6 points on the PHQ-9 or 5 points on the GAD-7.…”
Section: Methodsmentioning
confidence: 98%
“…Telecommunication technologies, especially video, have been judged as effective means of providing both assessments and interventions for individuals presenting with conditions including, but not limited to, anxiety, depression, obsessive–compulsive disorder, trauma, behaviour concerns, weight, and substance use (Bashshur et al, 2016; Berryhill, Culmer, et al, 2019; Berryhill, Halli-Tierney, et al, 2019; Cullum & Grosch, 2013; Hilty et al, 2017; Jensen et al, 2019) across ages, races, ethnicities, and countries (Gurney et al, 2021; Kassam-Adams et al, 2019; Whitley & Yahia, 2021). More importantly, when adapted in line with evidence-informed literature, services have been suggested to yield similar clinical outcomes as those achieved in in-person care (Hadjistavropoulos et al, 2022). Evolution of the technology and practices have also allowed for the establishment and maintenance of therapeutic alliance comparable to in-person methods (e.g., video; Goldstein & Glueck, 2016; McLean et al, 2021; Rees & Maclaine, 2015; Simpson et al, 2016; Turvey, 2018).…”
Section: Understanding Psychology-related Telehealthmentioning
confidence: 99%
“…In addition, evidence from 1 noninferiority trial suggests that in-person and remotely-delivered ACT for pain produce comparable outcomes 23 . Before the pandemic, however, remotely-delivered PMPs were not widely implemented, with notable exceptions 24 . Research is therefore needed to understand the effectiveness of remotely-delivered PMPs implemented in real-world practice where patients present with greater complexity 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Before the pandemic, however, remotely-delivered PMPs were not widely implemented, with notable exceptions 24 . Research is therefore needed to understand the effectiveness of remotely-delivered PMPs implemented in real-world practice where patients present with greater complexity 24 . Crucially, implementation must consider the local context, including permitted technological platforms, staff resources, and support to sustainably deliver and continuously improve remote treatment 25–27 …”
Section: Introductionmentioning
confidence: 99%